Positive effects of an invasive shrub on aggregation and abundance of a native small rodent - Malo, A; Godsall, B; Prebble, C; Grange, Z; McCandless, S; Taylor, A; Coulson, T (2013)
Invasive plants can have dramatic effects on natural ecosystems. It is unclear, though, whether these will have a positive or negative effect on animal species' behavior and population parameters within ecosystems where invasive plants occur. Here, we use a 2-year time series of mouse trapping data to test the effects of an evergreen invasive shrub, Rhododendron ponticum, on population distribution and abundance in a population of wood mice (Apodemus sylvaticus) in southern England. Given the importance of aerial predators on rodent survival and the shield that the thick cover of Rhododendron branches and leaves provides, we predicted that Rhododendron would have a positive effect on mouse aggregation and abundance. The results confirmed both predictions: proximity to Rhododendron positively influenced mouse abundance, whereas a significant interaction between protective microhabitat features (logs) and Rhododendron suggest that reductions in predation risk drive the proximity results. In addition, as mouse densities increased, competition increased. During spring, when mouse territoriality was greatest, we found primarily large adults in the Rhododendron habitat, with subadult and juvenile mice more likely to be found away from Rhododendron patches. The effects of Rhododendron-driven increases in mouse density on lower (seed predation and dispersal) and upper trophic level (weasel populations) are also discussed. Questing tick's density and invertebrate biomass were also lower under Rhododendron. Our research shows that an invasive plant species can increase the abundance of a native mammal and that this could potentially lead to increases/decreases in other species populations within the community. © 2012 The Author.